Large Future Increase in Exposure Risks of Extreme Heat Within Southern China Under Warming Scenario - Cao, Ning; Li, Gen; Rong, Meiyan; Yang, Jinyi; Xu, Feng (Frontiers in Earth Science, 2021)
With the continued global warming, quantifying the risks of human and social-economic exposure to extremely high temperatures is very essential. The simulated extreme high-temperature days (EHTDs) with a maximum temperature higher than 35C (38C, 40C) in Southern China during 1980-1999 and 2080-2099 are analyzed using the NEX-GDDP dataset. By comparing the climatology of the two scenario periods, the multi-model ensemble mean patterns show that EHTDs will greatly increase at the end of the 21st century, and its center at 35C is projected to shift to Guangxi from Jiangxi. Model diversities are fairly small, and the spread increases with T-level rises. EOF analysis shows that the 100-year warming will impact the southern part greater than the northern part. Trend patterns exhibit comparable results to models, but with a relatively large spread. The population and economy exposure to extremely high temperatures are calculated, showing that they both will experience a large increase in future projected decades. In historical decades, the growth of population and GDP have dominated the increasing exposure risks, but these effects weaken with the T-level increases. In future decades, climate change plays a leading role in affecting the exposure, and its effect strengthens with the T-level increases. For historical to future changes, the dominant contributor to population exposure changes is the climate factor(~74%), while substantially 90% contribution to economy exposure changes is dominated by the combined effects of climate and economy growth.